Ethnic Disparity in Mortality Among Ischemic Heart Disease Patients. A-20 Years Outcome Study From Israel - Abu-Much, Arsalan; Nof, Eyal; Bragazzi, Nicola Luigi; Younis, Anan; Hochstein, David; Younis, Arwa; Shlomo, Nir; Fardman, Alexander; Goldenberg, Ilan; Klempfner, Robert; Beinart, Roy (Frontiers in Cardiovascular Medicine, 2021)
Background Long-term morbidity and mortality data among ischemic heart disease (IHD) patients of different ethnicities are conflicting. We sought to determine the independent association of ethnicity and all-cause mortality over two decades of follow- up of Israeli patients. Methods Our study comprised 15,524 patients including 958 (6%) Arab patients who had been previously enrolled in the Bezafibrate Infarction Prevention (BIP) registry between February 1, 1990, and October 31, 1992, and subsequently followed-up for long-term mortality. We compared clinical characteristics and outcomes of Israeli Arabs and Jews. Propensity score matching (PSM) (1:2 ratios) was used for validation. Results Arab patients were significantly younger (56±7 years vs. 60±7 years; p<0.001; respectively), and had more cardiovascular disease (CVD) risk factors. Kaplan-Meier survival analysis showed that all-cause mortality was significantly higher among Arab patients (67% vs. 61%; log-rank p<0.001). Multivariate adjusted analysis showed that mortality risk was 49% greater (HR 1.49; 95% CI ;1.37-1.62, P value <0.001) among Arabs. Conclusions Arab ethnicity is independently associated with an increased 20-year all-cause mortality among patients with established IHD.